(3eUGQY GdeUGQYs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3eMeO Hf YHO GdcQje Hf CMeO GdTgQSJGfj,J (B548 (3g` s ((3GdeOQSI GdfGUQjI s)
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf hHYO aEfi dTZai HGdYdhe GdYbdjI cfJ ChbGJ aQGZi GfXQ ai cJH YdeGFgG hGbJVi cdGe GdfGXQjf ajgG s
(3BNQgG (B:s
(3Cbhd cdeG jJYdb HGdHOf hbO jchf HGdYbd ai cd hLg gPG BNQ eG ChQOg GdeUGQY ai eUGQYJg hGdMeO ddg QH GdYGdejf s
(3hQO GdYfhGf GdCUdi ai cX (B2/ 1703s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(269) s
Keywords: (3GdJhMjO hGdedd hGdfMds